Deixis in Raya and The Last Dragon Movie Script - Asrawi Sahidin; Sudirman Maca; Andi Tenri Abeng (Humaniora: Journal of Linguistics, Literature, and Education, 2022)
Some difficulties of the speakers in using the diexis in the social interaction, and make the speakers misunderstand the message of utterances. The research aimed to find out the types and function of deixis in the Raya and The Last Dragon movie script. The deixis are always found in the daily interaction. The deixis were analyzed in the interaction or the utterance in which related to the people, something, place and time. The research applied qualitative descriptive through pragmatic approach in analyzing the data. The data were obtained by reading, identifying, highlighting the words that contained deixis in the utterance based on Levinson theory. The results show that there were five types of deixis used in movie script namely person deixis, time deixis, place deixis, discourse deixis and social deixis. Person deixis was the most dominant types used in movie script. Every deixis has different functions based on the types of deixis such as: person deixis has 6 functions, time deixis has 3 functions, place deixis has 3 functions, discourse deixis has 2 functions and social deixis has 5 functions.